Hospital digital transformation: Implementation of a dashboard for advanced management in an Intensive Care Unit (ICU) (Research, Society and Development, 2025)
Faced with the challenging scenario of Intensive Care Units (ICUs), where seriously ill patients require highly specific care, the importance of Information and Communication Technologies (ICTs) for improving processes and effective data management stands out. In this context, the problems lie in the potential difficulties in managing Electronic Health Records (EHRs), indicators, protocols, communication and resources. This reality highlights the relevance of this research in the international context, highlighting Brazil's delay in innovations in the area of health. Furthermore, there is a need for alignment with the United Nations (UN) Sustainable Development Goals (SDGs) and the importance of harmonizing the theme with organizational strategic planning, updating efficiency, safety, quality and results in critical environments. of health. The main objective of this research was to develop a control panel that would integrate indicators for advanced management in the ICU of a private hospital in Rio Grande do Norte, accredited by the National Accreditation Organization (ONA). This research will adopt a quantitative and qualitative approach, characterized as applied, with descriptive and explanatory objectives. Methods include action research. The result made it possible to analyze the data from the neonatal, adult and pediatric ICUs for 24 months (2023 and 2024) on the dashboard, and to draw up a replicability plan. This progress represented a substantial milestone in the hospital's digital transformation, with the aim of improving the effectiveness and quality of healthcare, as well as enabling implementation in other hospitals.